KEMAMPUAN INPLEMENTASI MENAJEMEN PEMERINTAHAN, SIKAP KERJA, MOTIVASI KERJA DAN EFEKTIFITAS KERJA. - ', Slamet Riyadi (Jurnal Ilmu Administrasi Negara, 2014)
The Ability Governance Implementation Management, Work Attitude, Work Motivation and Work Effectiveness. This study aims to determine the effect of the implementation of government management ability, work attitude and motivation to work on the effectiveness of the headman, either partially or jointly. This research uses descriptive quantitative method with correlation and regression statistical analysis. The study population was urban village located in Depok were 63 wards. Samples were taken 15 villages with a random sampling technique. Techniques of data collection using a questionnaire based on the perception of the respondents according to a Likert scale. Data analysis was performed in two ways: descriptive analysis and inferential analysis. The results showed that the ability of the implementation of government management, work attitude and work motivation headman, either partially or jointly have influence on the effectiveness of the headman significant and positive. The dominant influence on the effectiveness of the headman is variable work motivation. But the overall effect of the implementation of the ability of government management, work attitudes, work motivation on the effectiveness of 0.707 and in other words the effectiveness of work contribution headman only 49.9%. The remaining 50.1% is determined by other factors such as employee loyalty, personality and expertise, and for the further research needs to be done in connection with the performance of employees. Keywords: government management implementation ability, work attitude, work effectiveness.